"And Then the Rest Happened"— A Qualitative Exploration of the Role that Meaningful Activities Play in Recovery Processes for People with A Diagnosis of Substance Use Disorder. Issue 1 (December 2022) - Veseth, Marius; Svendsen, Thomas Solgaard; Nesvaag, Sverre; Moltu, Christian; Davidson, Larry; Bjornestad, Jone
Background : In this qualitative exploration, we report on a thematic analysis of the key role that engaging in meaningful activities may play in recovery processes for people with a diagnosis of substance use disorder (SUD). Methods: We conducted semi-structured, individual interviews with 30 participants and analyzed the parts of this material that were related to meaningful activities. Results: The findings are summarized through the development of three broad themes: (a) the central role of work—"The wages suck, but the job is gold"; (b) mastery and commitment—"I had to get up early, find my spot, I had to be present and fully functioning all day"; and (c) repairing the bridge to community life—"It's my job and working out that has made this possible, really, I see that now." Conclusion: We discuss these findings in relation to a recovery perspective and relevant empirical studies, highlight some important implications for research and practice, and consider the strengths and limitations of the present study.